Planning in Islamic Management as an Instrument to Achieve Maqashid Syariah from the Perspective of Hadith Studies: Perencanaan dalam Manajemen Islam sebagai Instrumen untuk Mencapai Maqashid Syariah dari Perspektif Studi Hadis - Maliki, Emil; Nasuki, Abdul Hay; Mumtazi; Fachriandy, Andy; Muhsin, M Syaripuddin; Hakiki, Ikrar Rafi; Abdullah, Bahruddin; Falahudin, Iwan; Muhsin, Masrukhin (Direktorat Pondok Pesantren Universitas Islam Indonesia, 2026)
Planning is one of the fundamental functions in Islamic management and plays a strategic role in directing organizational activities so that they run effectively and efficiently in accordance with sharia values. From an Islamic perspective, planning is not solely oriented toward the achievement of worldly goals, but is also aimed at realizing the maqāṣid al-sharī‘ah, namely the protection of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl). This article aims to analyze the concept of planning in Islamic management as an instrument for achieving the maqāṣid al-sharī‘ah through the perspective of hadith studies. The research method employed is library research with a qualitative-descriptive approach, conducted through the exploration and analysis of the hadiths of the Prophet Muhammad (peace be upon him) related to the principles of planning, prudence, time management, and strategy in various aspects of life. The findings indicate that the Prophet’s hadiths, both implicitly and explicitly, contain principles of planning that are systematic, visionary, and oriented toward public benefit (maṣlaḥah), such as the importance of intention, preparation, prioritization, and consideration of long-term impacts. These principles are consistent with the objectives of the maqāṣid al-sharī‘ah and can serve as a normative foundation for contemporary Islamic management practices. Therefore, planning in Islamic management functions not only as a technical managerial tool but also as a strategic instrument for realizing the welfare of the ummah in accordance with the guidance of the Prophet’s hadiths. (Perencanaan merupakan salah satu fungsi fundamental dalam Perencanaan merupakan salah satu fungsi fundamental dalam manajemen Islam dan memiliki peran strategis dalam mengarahkan aktivitas organisasi agar berjalan secara efektif dan efisien sesuai dengan nilai-nilai syariah. Dalam perspektif Islam, perencanaan tidak hanya berorientasi pada pencapaian tujuan duniawi, tetapi juga diarahkan untuk mewujudkan maqāṣid al-sharī‘ah, yaitu perlindungan terhadap agama (ḥifẓ al-dīn), jiwa (ḥifẓ al-nafs), akal (ḥifẓ al-‘aql), keturunan (ḥifẓ al-nasl), dan harta (ḥifẓ al-māl). Artikel ini bertujuan untuk menganalisis konsep perencanaan dalam manajemen Islam sebagai instrumen untuk mencapai maqāṣid al-sharī‘ah melalui perspektif studi hadis. Metode penelitian yang digunakan adalah studi kepustakaan (library research) dengan pendekatan kualitatif-deskriptif, yang dilakukan melalui penelusuran dan analisis hadis-hadis Nabi Muhammad ﷺ yang berkaitan dengan prinsip-prinsip perencanaan, kehati-hatian, manajemen waktu, dan strategi dalam berbagai aspek kehidupan. Hasil penelitian menunjukkan bahwa hadis-hadis Nabi, baik secara implisit maupun eksplisit, mengandung prinsip-prinsip perencanaan yang sistematis, visioner, dan berorientasi pada kemaslahatan umum (maṣlaḥah), seperti pentingnya niat, persiapan, penentuan prioritas, serta pertimbangan dampak jangka panjang. Prinsip-prinsip tersebut selaras dengan tujuan maqāṣid al-sharī‘ah dan dapat dijadikan sebagai landasan normatif dalam praktik manajemen Islam kontemporer. Dengan demikian, perencanaan dalam manajemen Islam tidak hanya berfungsi sebagai alat manajerial teknis, tetapi juga sebagai instrumen strategis dalam mewujudkan kesejahteraan umat sesuai dengan tuntunan hadis Nabi.)